2020
DOI: 10.15244/pjoes/104660
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Risk Assessment of Urban Streams Using Fish Biomarkers of DNA Damage and Physiological Responses

Abstract: Ecological risk assessment was carried out in two urban streams, viz. Gap Stream (GS) and Miho Stream (MS), in the Geum River Watershed during July 2013-October 2014. The techniques used in this study included multi-level fish biomarkers of DNA damage based on single-cell gel electrophoresis (SCGE) coupled with the study of physiological responses based on 7-ethoxyresorufin-O-deethylase (EROD) and acetylcholinesterase (AChE) activities in fish species. Biomarker values of tail DNA (tDNA), tail length (T L), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 49 publications
1
10
0
Order By: Relevance
“…The distribution of study sites in each sub-watershed in Geum River watershed based on mmIBI 08 model confirmed the majority of sites categorized under the fair (F) and poor (P) categories after obtaining the individual site scores ( River reflected severely deteriorating ecological health that also corresponded with degrading water chemistry in these watersheds. The majority of study sites displayed huge decline in the total number of native fish species in approximation to the decline of the total number of native individuals as well as the number of sensitive species (SS), which is an unambiguous indication of degrading biological health [35,41,50,59,60]. The proportion of omnivorous fish species showed an increase in the majority of sites and similar was the case with the proportion of individuals as native insectivores that yet again indicated the declining ecological health [2,5,17,35,59].…”
Section: Watershed Assessment Based On the Mmibi 08 Modelmentioning
confidence: 99%
“…The distribution of study sites in each sub-watershed in Geum River watershed based on mmIBI 08 model confirmed the majority of sites categorized under the fair (F) and poor (P) categories after obtaining the individual site scores ( River reflected severely deteriorating ecological health that also corresponded with degrading water chemistry in these watersheds. The majority of study sites displayed huge decline in the total number of native fish species in approximation to the decline of the total number of native individuals as well as the number of sensitive species (SS), which is an unambiguous indication of degrading biological health [35,41,50,59,60]. The proportion of omnivorous fish species showed an increase in the majority of sites and similar was the case with the proportion of individuals as native insectivores that yet again indicated the declining ecological health [2,5,17,35,59].…”
Section: Watershed Assessment Based On the Mmibi 08 Modelmentioning
confidence: 99%
“…Aquaculture is mainly divided into extensive and intensive types based on water quality and feed inputs (Ray et al, 2021;Jewel et al, 2020). The yield of a comprehensive system is meagre due to a lack of knowledge, required facilities, poor water quality and its management, and not exploring the locally available cheap feed ingredients (Atique et al, 2020a;Bae et al, 2020). However, intensive aquaculture applies the latest pond structure technologies, feeding, stocking density, etc., for the high yield of aquatic organisms (Haider et al, 2018;Iqbal et al, 2020a, b).…”
Section: Introductionmentioning
confidence: 99%
“…Tropical estuarine ecosystems are dependable indicators of environmental change (Dauvin, 2007); therefore, species composition and structure are the sensitive community features that modify in reaction to habitat level changes (Post et al, 2006;Lefrere et al, 2015;Atique and An, 2020). The higher the species diversity and abundance, the higher productivity and available feeding resources ensured (Day et al 1989;Iqbal et al, 2017;Iqbal et al, 2020;Moon et al, 2020;Bae et al, 2020). For instance, the temporal variations in benthic macrofauna composition in response to seasonal variation in a tropical coastal lagoon of the Gulf of Mexico are reflected in the community compositions (Hernández-Guevara et al, 2008).…”
Section: Introductionmentioning
confidence: 99%